Henoch-Schönleinova purpura pri odraslem - Skačej, Helena (Acta medico-biotechnica, 2009)
Background: Henoch-Schonlein purpura (HSP) is a systemic inflammation of small-vessel walls that predominantly affects children. In adults, on the other hand, it appears rarely, and can be more severe. The disease is characterised by a tetrad of clinical signs which manifest the skin, joint, gastrointestinal, and kidney involvement. HSP is diagnosed using internationally-accepted criteria. At present, there is no effective specific therapy for children and adults. However, in cases of severe organ involvement, aggressive treatment may stabilise the disease. Case report: We present a case of a 59-year-old immunologically uncom- promised patient with an extremely severe form of HSP. Epidemiology, etiopathogenesis, clinical features, diagnostic procedures, differential diagnosis, treatment, and prognosis of the disease are discussed. Conclusions: The patient was treated with corticosteroids, human polyspecific immunoglobulins, and immunosuppressive agents. A satisfactory clinical remission has been achieved.
Keywords: dermatologija; diagnosis; Diagnostika; Purpura, Schoenlein-Henoch; Schoenlein-Henochova purpura; Signs and Symptoms; sistemski vaskulitis; therapy; vnetja; Zdravljenje; Znaki in simptomi